2005
DOI: 10.1055/s-2005-917125
|View full text |Cite
|
Sign up to set email alerts
|

When Silence Is Not Golden: An Integrated Approach to Selective Mutism

Abstract: Selective mutism (SM) is a rare disorder that is associated with both anxiety and communication impairments. Preliminary evidence suggests that educational attainment and development of social skills and self-esteem may be affected by SM in a significant proportion of cases. There is a critical need for cross-disciplinary research from the fields of speech-language pathology, psychiatry, and clinical psychology to develop protocols for assessing language and cognitive functioning in children with SM and develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This is in line with some previous studies, [16,37,38] although other clinical reports have shown only a slightly higher prevalence in girls [39,40] or comparable rates between sexes. [30,35,41] It has been argued that such differences in rates across sexes is due to social perceptions of "shy" or "anti-social" behavior, [42] or due to setting in which diagnosis is made. [30] The cultural beliefs around "shyness" [43] are also likely to contribute to under diagnosis of SM in general.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with some previous studies, [16,37,38] although other clinical reports have shown only a slightly higher prevalence in girls [39,40] or comparable rates between sexes. [30,35,41] It has been argued that such differences in rates across sexes is due to social perceptions of "shy" or "anti-social" behavior, [42] or due to setting in which diagnosis is made. [30] The cultural beliefs around "shyness" [43] are also likely to contribute to under diagnosis of SM in general.…”
Section: Discussionmentioning
confidence: 99%
“…A further limitation concerns the issue that most studies examining SM have largely been informed by parent report despite the recommendation that a multi-method, multiinformant approach be utilized in the assessment of anxiety disorders (Schniering et al 2000) and SM (Mclnnes and Manassis 2005). Given the personal nature of fears, selfreport is a recommended component of the multi-modal battery (Schniering et al 2000).…”
mentioning
confidence: 98%
“…Although there is no coded gold standard for SM treatment, we could assume that treating anxiety in order to improve speech could appears to be an aetiologically suggestive therapeutic option, [51,52] although the evidence of the pharmacological effect some drugs is undeniable [53,54]. Unfortunately, in pediatric age the pharmacotherapy cannot be recommended as the first choice of treatment and the nonpharmachological approachs could be considered more suitable and more accepted by parents.…”
Section: Discussionmentioning
confidence: 99%